PASTORAL KONSELING BAGI ORANG SAKIT - Roma Sihombing (Institut Agama Kristen Negeri Tarutung, 2019)
AbstractHuman life which is very complex with all its activities adds to the problems that must be faced which tend to plunge into pain and stress. The servants and administrators of the church today are not only required to be able to deliver the word of God, but also must be able to provide pastoralcounseling services. This study aims to examine and understand howpastoral counseling is for the sick. The method used is a qualitative methodor library research, with the research strategy analyzing various literatures related to the title of this paper. This research found, how pastoral counseling for sick people, so they can be helped and recovered from the disease they experienced. Services can be done in various ways such as, door-to-door visits, face-to-face meetings, which are carried out by thecounselor by: understanding (understanding attitude of the counselor), andResponding (giving constructive responses). Pastoral counseling for the sickwill be better if we remember that counselors take part in the work of Godand his body in this world to penetrate the isolation and alienation of thesick. Therefore, pastoral counseling will be better if we remember that thefocus of pastoral care is the person we are accompanying.Keywords: Pastoral Counseling, the Sick